Comparative Analysis of the Anti-inflammatory Effects of E-MTA, Ketac-E, and Sealapex on Human Periodontal Ligament Stem Cells - Ayesha Imtiaz; Kiran Nayyar; Khadija Akhtar; Muhammad Yousuf Ali; Naresh kumar; Ehsan Ul Haq (Pakistan Journal of Medicine and Dentistry)
Background: Root Canal Treatments play a critical role in managing periapical and pulp diseases, but failure to control the inflammation may result in treatment failure. Newer developments have targeted anti-inflammatory bioactive sealers as potential contenders. The objective of this study was to explore the anti-inflammatory potential of Endoseal E-MTA (E-MTA), Ketac-Endo (Ketac-E), and Sealapex (S-apex) on cultured Human periodontal ligament stem cells.